Design Errors in Public Pension Systems: The Case of Hungary - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
This paper discusses design errors in public pension systems, using Hungary as an illus-tration. When the communist political and economic system was replaced by democracy and market economy, the subsequent governments had even greater difficulties in de-signing consistent pension reforms than before. Double-digit inflation and deep decline in real wages called for indexation and valorisation of pensions. In addition to arbitrary pub¬lic policy, poorly designed rules even amplified the errors of the public pension system, creating notch cohorts and disadvantaged strata.
Keywords: H1; H8; 330; public pension system; social security; Hungary; design errors